Nursing Leaders’ Knowledge and Awareness of Bullying and Lateral Violence: A Qualitative Study - Corina Elena Luca MScN, BScN; Giovanna Pezzoli MScN, BScN; Stefan Kunz PhD, MSc, BSc (Hons); Monica Bianchi PhD, EMBA, MScN, RN (SAGE Open Nursing, 2024)
Introduction Bullying and lateral violence are prevalent phenomena within the nursing profession, exerting significant impacts on patient safety, the nursing profession and the organisation. The pivotal role of nurse leaders is paramount in both the prevention and resolution of these issues. Aim The aim is to explore the level of awareness and knowledge of bullying and lateral violence of nurse leaders in a public hospital in Switzerland. Methods A qualitative descriptive study has been conducted. Data were collected from February to August 2020 using semi-structured interviews and focus groups that were recorded and transcribed verbatim. Two researchers independently utilised Braun and Clarke's thematic analysis to code, categorise and synthesise the data. The sample of nursing middle-management leaders was purposive. Results The study involved 35 nurse leaders as participants. Through data analysis, 15 themes were identified, which were further grouped into five major themes: characteristics of the phenomena, facilitating and hindering factors, emotions/experiences, strategies and supports. The results highlighted that nurse leaders may have a lack of knowledge about these phenomena, leading to challenges in their identification. The awareness achieved by the nurse leaders highlighted their need to understand what they were ‘fighting against’. Conclusion It is essential to consider the impact of these phenomena on employees’ well-being and their potential consequences for patient safety, quality of care and financial performance. A preventive approach by increasing nurse leaders’ competence in observing everyday working realities and identifying strategies for addressing bullying is required. Further research on the construction and implementation of specific interventions is essential, aimed at preventing and addressing these phenomena comprehensively.